Comprehensive Management Strategies for Fig Rust Disease in Ficus carica: An Integrated Approach - Yogesh C. Khot; Sulochana Rathod; Radha Ghuge (The Bioscan, 2024)
Fig rust, caused by the fungus Cerotelium fici, poses a significant threat to Ficus carica cultivation, leading to reduced leaf area, premature defoliation, and compromised fruit quality. This study presents a comprehensive review of management strategies for fig rust, emphasizing an integrated approach that combines cultural, chemical, and biological methods. Key strategies include the application of fungicides, timely irrigation practices, and the removal of infected plant debris. Additionally, the study explores the potential of biocontrol agents and resistant fig cultivars as sustainable solutions. The findings highlight the importance of a multi- faceted approach to effectively mitigate fig rust, ensuring improved fig tree health and productivity.